Analisis Manajemen Produksi pada PT Pilihanmu Indonesia Jaya - Dafa Firmansyah Hidayat; Taat Kuspriyono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to analyze production management at PT Pilihanmu Indonesia Jaya in the workshop and coaching project. The study encompasses various critical stages, including market research and analysis, product strategy development, and the structured development of a product roadmap. The research methodology involves in-depth interviews with prospective users and stakeholders, as well as market data analysis to identify the needs and desires of the target audience. The findings indicate that personalization and high interactivity features are top priorities in product development. The implementation of collaboration tools such as Google Docs, Draw.io, and Figma facilitates effective communication and coordination between the UI/UX, front-end, and back-end teams. With a data-driven approach and a clear strategy, this workshop and coaching project has significant potential to meet market expectations and deliver substantial value. The study concludes that good production management, supported by cross-functional collaboration and the appropriate use of technology, is the key to successful development of innovative products that are relevant to user needs.